Direct interfaces for smart skins based on FPGAs - Oballe-Peinado, Óscar; Castellanos-Ramos, Julián; Hidalgo-López, José Antonio; Vidal-Verdú, Fernando (SPIE digital library, 2009)
Many artificial skins for robotics are based on piezoresistive films that cover an array of electrodes. Local preprocess- ing is a must in these systems to reduce errors and interferences and cope with the large amount of data provided by the sensor. This paper presents circuitry based on an FPGA to implement the interface to the artificial skin. The approach con- sists of a direct connection. The analog to digital conversion procedure is simple. It consists of measuring the discharging time of a capacitor through the resistance we want to read. This first proposed approach needs isolated tactels, so the raw sensor has to be fabricated in this way. If the tactile array is large, the strategy is not feasible. For instance, up to 288 pins are required to implement the interface with an array of 16x16 tactels. The proposal of this work for this case is to replace passive integrators by active ones. The result is a circuitry that allows the cancellation of interferences due to parasitic resis- tors and the sharing of the addressing tracks. Moreover, the FPGA allows the processing of data from the tactile sensor at a very high rate. This is because the high number of I/O pins of the device allows the conversion of many channels (in our case one per column) in parallel. The internal processing of the tactile image can also be done in parallel. This means we could be able to respond to very high demanding tasks in terms of dynamic requirements, like slippage detection. This also means we can run complex algorithms at real time, so a smart, programmable and powerful sensor is obtained.
Keywords: Tacto; Detectores; FPGA; Tactile sensors; Local pre-processing